Analisis Kemampuan Dosen Uinsu Dalam Menyusun Rps Berbasis Obe Pada Rumpun Mata Kuliah Pai - Ridha Khairani; Izzatussyakira; Ismail Amnur; Siti Halimah (Yayasan pendidikan dzurriyatul Quran, 2026)
The paradigm shift in higher education curricula toward Outcome-Based Education (OBE) requires lecturers to possess adaptive pedagogical competencies, particularly in designing Semester Learning Plans (Rencana Pembelajaran Semester/RPS). This study aims to analyze the ability of lecturers at the State Islamic University of North Sumatra (Universitas Islam Negeri Sumatera Utara/UINSU) in developing OBE-based RPS within the Islamic Religious Education (PAI) course cluster, which includes the courses of PAI Learning Strategies, Hadith Studies, and History of Islamic Education. This research employed a descriptive qualitative method using document analysis and confirmation interviews with course instructors. The findings reveal that: (1) in the input stage, the formulation of Program Learning Outcomes (CPL) into Course Learning Outcomes (CPMK) and Sub-Course Learning Outcomes (Sub-CPMK) by Izzatussyakira has generally reflected the use of Bloom’s Taxonomy action verbs, although further alignment with higher-order thinking skills (HOTS) is still required; (2) in the process stage, the selection of learning materials and instructional strategies in the PAI Learning Strategies course has adopted a student-centered learning (SCL) approach, whereas the Hadith Studies course taught by Ismail Amnur remains predominantly characterized by expository teaching methods; and (3) in the output stage, the design of evaluation methods, the accuracy of assessment instruments (rubrics), and the updating of references based on reputable academic journals require further improvement. Overall, lecturers’ pedagogical competence in developing OBE-based RPS can be categorized as fairly good; however, structured workshops on constructive alignment are necessary to enhance the quality and consistency of curriculum implementation.